2002
DOI: 10.1093/carcin/23.6.1079
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid, B and T lymphoid and mixed lineage thymic lymphomas in the irradiated mouse

Abstract: Thymic lymphoma is a very common spontaneous and/or induced malignancy in both inbred mice and in transgenic mouse models of human cancer. Although a thymic lymphoma is defined as thymus-dependent T-cell malignancy, diagnostic criteria vary between studies and considerable heterogeneity has been reported. To define and classify the thymic lymphomas that arose in our study of X-irradiated (CBA/HxC57BL/6)F1, F1 backcross and F1 intercross mice, 66 thymic lymphomas were immunogenotyped for immunoglobulin heavy ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In the current study, an even more considerable loss of methylation was observed in the thymus tissue. The spleen and thymus are important parts of hematopoietic and lymphatic tissue and are profoundly affected in lymphomas and leukemias (31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, an even more considerable loss of methylation was observed in the thymus tissue. The spleen and thymus are important parts of hematopoietic and lymphatic tissue and are profoundly affected in lymphomas and leukemias (31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…The murine model is widely used, well characterized, and generally accepted for studies of radiation-induced changes in hematopoietic and lymphatic tissue (31)(32)(33). Handling and care of animals was in strict accordance with the recommendations of the Canadian Council for Animal Care and Use.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Spleen and skin tissue located above spleen were sampled upon sacrifice and processed for further molecular studies. Both spleen and skin are radiation targets organs and are linked to radiation carcinogenesis [Shore, 1990;Boulton et al, 2002].…”
Section: Animal Model and Irradiation Of Animalsmentioning
confidence: 99%